2016
DOI: 10.1038/mp.2016.225
|View full text |Cite
|
Sign up to set email alerts
|

Role of the adipose PPARγ-adiponectin axis in susceptibility to stress and depression/anxiety-related behaviors

Abstract: Adaptive responses to stressful stimuli involving behavioral, emotional and metabolic changes are orchestrated by the nervous and endocrine systems. Adipose tissue has been recognized as a highly active metabolic and endocrine organ, secreting adipokines that operate as hormones to mediate the crosstalk with other organs including the brain. The role of adipose tissue in sensing and responding to emotional stress and in behavioral regulation, however, remains largely unknown. The nuclear receptor peroxisome pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 87 publications
(117 reference statements)
0
77
0
1
Order By: Relevance
“…Peroxisome proliferator‐activated receptor γ (PPARγ) is a ligand‐activated transcription factor that belongs to the nuclear receptor family and a master modulator of glucose and lipid metabolism, organelle differentiation, and inflammation (Guo et al., 2017; Zhao et al., 2016). These form heterodimers with the retinoid X receptor and bind to peroxisome proliferator response elements (PPREs) in the promoter region of respective target genes (Hallenborg et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxisome proliferator‐activated receptor γ (PPARγ) is a ligand‐activated transcription factor that belongs to the nuclear receptor family and a master modulator of glucose and lipid metabolism, organelle differentiation, and inflammation (Guo et al., 2017; Zhao et al., 2016). These form heterodimers with the retinoid X receptor and bind to peroxisome proliferator response elements (PPREs) in the promoter region of respective target genes (Hallenborg et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PPARγ by troglitazone and pioglitazone reduces infarct volume by improving neurological function following middle cerebral artery occlusion in rats (Corona & Duchen, 2016; Culman, Zhao, Gohlke & Herdegen, 2007). Also, PPARγ activation by rosiglitazone imparts antidepressant‐ and anxiolytic‐like effects (Guo et al., 2017). …”
Section: Introductionmentioning
confidence: 99%
“…33,34 It has also been found that the PPAR γ agonist rosiglitazone imparts antidepressant-and anxiolytic-like effects. 28 Sun et al 35 found that PPAR γ agonist prevents neuronal loss and attenuates development of spontaneous recurrent seizures (SRS) through BDNF/TrkB signaling following pilocarpine-induced status epilepticus, and another report supports the idea that PPARγ agonist might be a potential neuroprotective agent for epilepsy by inhibiting oxidative stress and preventing astrocyte activation. 36,37 However, the role of the PPAR γ agonist rosiglitazone in protection against epilepsy from the point of microglia remains unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Peroxisome proliferator‐activated receptor γ (PPAR γ) is a major modulator of lipid and glucose metabolism, inflammation, and organelle differentiation and has been suggested to play important roles in many neurological disorders . PPAR γ is a ligand‐activated transcription factor that belongs to the nuclear receptor family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation